Perancangan Board Game Sebagai Media Untuk Melestarikan Kue Tradisional Nusantara Kepada Anak-Anak - Grasella Davina Audria; Irwan Harnoko; Nugroho Widya Prio Utomo (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Indonesia has a variety of traditional Nusantara cakes that are not only unique, but also appetizing. However, along with the development of the times, traditional Nusantara cakes are increasingly rare. Only a handful of sellers are still loyal to selling these snacks. One of the reasons for the decline in the popularity of these traditional cakes is the growing perception among the public, especially children, who consider these cakes "old-fashioned." Many elementary school-aged children are now more interested in modern snacks, such as donuts, cakes, or candy, than traditional cakes such as klepon, onde-onde, or layered cakes. Therefore, this study aims to design a board game as a fun and educational interactive media, with the hope of introducing and preserving traditional Nusantara cakes to children aged 8-11 years. The methods used in this study include an in-depth analysis of relevant traditional cakes, development of game mechanics that are appropriate to the target age, and prototype trials to see children's responses and involvement in this game. Thus, this research is expected to provide a significant contribution to efforts to preserve culture while promoting a deeper understanding of the culinary richness of the archipelago among the younger generation, so that this tradition can continue to be passed down from one generation to the next.